Analysis of Noken System in Papua Elections: Implications for Democracy and National Political Stability: Analisis Sistem Noken dalam Pemilu Papua: Implikasi bagi Demokrasi dan Stabilitas Politik Nasional - Muh Alghifari; Hilmayanti Ilham; Nur Hijrih Awaliya Yashab; Fera Zabira Zahra (Journal of State Democracy, 2025)
The Noken system has been implemented since 2004 so that it has been 21 years since it has experienced challenges and obstacles in its implementation so far, this election system has become a specialty for Papua Province due to several factors including geography and culture, the Noken system is considered not in accordance with the principles of democracy and disrupts political stability so that the purpose of this article is to examine the implementation of the noken system on the quality of democracy and political stability. By using normative legal research methods, namely assessing the harmony between legal norms and implementation in society, the results of the study show that although the Noken System is strengthened through the Constitutional Court's decision, but what cannot be denied is the occurrence of fraud in this system which leads to disruption of political stability because the right to vote is considered not to be carried out transparently and there is no guarantee of a deliberation result represented in this system as the principle of general elections, so it is necessary to adapt to the principles of general elections, not to abolish this system and try to adapt it to the true values of democracy.